Policy Network Analysis in Poverty Alleviation Policies in Indramayu Regency (Pusat Riset dan Inovasi Nasional, 2025)
Policy networks play an important role in improving the effectiveness of poverty reduction policies, as they involve interaction and collaboration between local governments, non-governmental organizations (NGOs), the private sector, academics, and the community. This study aims to analyze the structure of policy networks and their influence on the effectiveness of poverty reduction programs in Indramayu Regency. The study uses a qualitative approach with a case study method, and data is collected through in-depth interviews, participatory observation, and documentation studies. The results show that limited collaboration between actors, uneven distribution of resources and information, variations in the capacity of non-governmental actors, and weak coordination and communication mechanisms are the main obstacles affecting the effectiveness and sustainability of the program. This study concludes that strengthening policy networks through collaborative forums, increasing actor capacity, sustainable coordination mechanisms, simplifying regulations, and collective learning can improve the effectiveness of poverty reduction policies. These findings contribute theoretically to the study of policy networks and provide practical recommendations for the governance of poverty reduction programs at the regional level.